RADIKALISME AGAMA PERSPEKTIF AL-QUR’AN DAN KONSELING - Irman Irman; Yusefri Yusefri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2018)
The term of radicalism often intersects with religion and not only on certain religions, but all the major religions in the world experience it. The radical actions that took place in the last few years in the name of Islam have tarnished Islam. Islam is a religion that teaches the importance of peace, ramatallilalamin, prohibits the acts of coercion in embracing religion, emphasizes tolerance, respects differences and does not justify acts of violence. Psychologically, the root cause of radical action is due to dissatisfaction with reality and accompanied by enthusiasm to make changes in its own way and principles. Anti-radicals behavior emerge, treatment counseling through the process of disputing, cognitive restructuring and reframing based on Islamic values.